2020
DOI: 10.1029/2020jb019946
|View full text |Cite
|
Sign up to set email alerts
|

Active Faulting, Submarine Surface Rupture, and Seismic Migration Along the Liquiñe‐Ofqui Fault System, Patagonian Andes

Abstract: The intra-arc Liquiñe-Ofqui Fault System (LOFS) is an active transpressive fault zone located in the Patagonian Andes of Chile. In 2007, a seismic sequence occurred in the Aysén Fjord region of Chilean Patagonia along the LOFS, with a M w 6.2 main earthquake that triggered dozens of landslides, some of which induced tsunami waves that caused severe damage and casualties. Through the analysis of high-resolution seismic reflection and bathymetric data, we identify six submarine faults cutting the Late Quaternary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…Our results also support the Kanamori and Rivera 24 M w 7.7 crustal strike slip dextral event in 1960 with clear long-term dextral displacements consistent with surface faulting as would be expected after a dextral strike slip surface rupture. This is important because until our study, no clear evidence of terrestrial LOFZ surface faulting was reported to support this idea, although submarine evidence suggest repeated events within the past 12 ka 25 . Perhaps then, the Chile Margin in Aysén is one end member of the oblique subduction systems on Earth with significant partitioning from the subduction zone to the surface faulting along the LOFZ and is thus similar in nature and in regards to rates to the Philippines fault (20 to 25 mm/year 16 ) and in stark contrast with the San-in shear zone in Japan in the upper plate of the Nankai subduction zone where no surface faults are known 24 ?…”
Section: Methodsmentioning
confidence: 66%
See 2 more Smart Citations
“…Our results also support the Kanamori and Rivera 24 M w 7.7 crustal strike slip dextral event in 1960 with clear long-term dextral displacements consistent with surface faulting as would be expected after a dextral strike slip surface rupture. This is important because until our study, no clear evidence of terrestrial LOFZ surface faulting was reported to support this idea, although submarine evidence suggest repeated events within the past 12 ka 25 . Perhaps then, the Chile Margin in Aysén is one end member of the oblique subduction systems on Earth with significant partitioning from the subduction zone to the surface faulting along the LOFZ and is thus similar in nature and in regards to rates to the Philippines fault (20 to 25 mm/year 16 ) and in stark contrast with the San-in shear zone in Japan in the upper plate of the Nankai subduction zone where no surface faults are known 24 ?…”
Section: Methodsmentioning
confidence: 66%
“…The fast slipping main trace of the LOFZ ruptures and causes major earthquakes (at least Mw 6.2 up to at least Mw 7.7; e.g. 24 , 25 ) and these surface ruptures cut all crustal rock units and Quaternary materials including bisecting volcanoes located along the LOFZ. The high-intensity and shallow upper crustal strong ground motions (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most other normal mechanisms are consistent with NE or WNW orientations (e.g., Events 3, 5, 9, and 11). Numerous NE oriented normal and dextral-normal faults have been observed along the SVZ (e.g., Cembrano & Lara, 2009;Pérez-Flores et al, 2016;Rosenau et al, 2006;Vargas et al, 2013;Villalobos et al, 2020), and similar focal mechanisms were detected during the 2007 Aysen swarm (Legrand et al, 2011;Russo et al, 2011). In particular, NE oriented faults and NE oriented lineaments have been found to be kinematically coupled with volcanoes and some of the minor eruptive centers located in the SVZ (Cembrano & Lara, 2009).…”
Section: Intra-duplex Domainmentioning
confidence: 86%
“…Crustal deformation in the SVZ is accommodated by two groups of faults: the LOFS and the ATF, as shown in Figure 1 (e.g., Cembrano et al, 1996; Cembrano & Lara, 2009; Melnick et al, 2006; Pérez‐Flores et al, 2016). The LOFS is an active fault system composed of NS oriented master faults with dextral and dextral‐reverse kinematics accompanied by NE to ENE oriented dextral and dextral‐normal faults (e.g., Arancibia et al, 1999; Iturrieta et al, 2017; Lange et al, 2008; Lavenu & Cembrano, 1999; Pérez‐Flores et al, 2016; Rosenau et al, 2006 ; Villalobos et al, 2020). Geological evidence indicates that the LOFS is a continental‐scale shear zone dominated by a transpressional regime, with a NS oriented dextral‐slip deformation that partially accommodates the margin‐parallel component of the plate‐convergence vector (see Figure 1).…”
Section: Tectonic Backgroundmentioning
confidence: 99%